2009
DOI: 10.4049/jimmunol.0803054
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Secrete the Immunosuppressive HLA-G Molecule upon CTLA4-Ig Treatment: Implication in Human Renal Transplant Acceptance

Abstract: CTLA4-Ig (Belatacept) is a new recombinant molecule that interferes with the signal of T lymphocyte activation and prevents acute rejection after renal transplantation. HLA-G acts as a naturally tolerogenic molecule in humans. In this study, we analyzed whether HLA-G contributes to CTLA4-Ig-mediated graft acceptance. Our results demonstrate that patients treated with CTLA4-Ig displayed significantly higher soluble HLA-G (sHLA-G) plasma concentrations (72 ± 14 ng/ml) than patients treated with calcineurin inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 48 publications
1
26
0
3
Order By: Relevance
“…In this regard, soluble HLA-G plasma levels were found to be enhanced after cyclosporine or tacrolimus administration in some heart transplant patients [51]. The effect of the immunosuppressive therapy on HLA-G expression was supported by recent results showing augmented HLA-G plasma levels in kidney transplant patients treated with the CTLA4-Ig fusion protein (Belatacept) [52]. This therapeutic agent is associated with better graft function and survival.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…In this regard, soluble HLA-G plasma levels were found to be enhanced after cyclosporine or tacrolimus administration in some heart transplant patients [51]. The effect of the immunosuppressive therapy on HLA-G expression was supported by recent results showing augmented HLA-G plasma levels in kidney transplant patients treated with the CTLA4-Ig fusion protein (Belatacept) [52]. This therapeutic agent is associated with better graft function and survival.…”
Section: Introductionsupporting
confidence: 53%
“…Considering the immunological role of HLA-G, many studies have demonstrated that HLA-G is a good prognostic factor for engraftment, not only in the context of pregnancy in which the fetus can be considered a semiallogeneic transplant but also in allogeneic transplants (heart, liver-kidney, kidney and lung transplants) [27,40,52,163]. Moreover, high HLA-G levels were recently associated with poor prognosis in various cancers [4,77,164,165].…”
Section: Hla-g-induced Tr Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…83 However, several experimental studies have shown the role of reverse signaling of CD80/CD86 in CTLA4-mediated coinhibition. 84 CTLA4-Ig binds to CD80/ CD86 molecules on dendritic cells and promotes the induction of the immunomodulatory enzyme indoleamine 2,3 dioxygenase 85,86 and the tolerogenic molecule HLA-G. 87 Experimental data suggest that reverse signaling of CD80/ CD86 also exists in B cells. 88,89 It is, therefore, tempting to speculate that, when belatacept binds to CD80/CD86, it directly influences the B cell fate.…”
Section: Belataceptmentioning
confidence: 99%
“…32 Immunotolerogenic stimuli, such as CTLA4-Ig, may further enhance HLA-G up-regulation. 36 Interestingly, the tryptophan catabolyzing enzyme indoleamine 2 3-dioxygenase (IDO) was shown to differentially modulate HLA-G expression in monocytes and myeloid DCs: IDO blocked HLA-G cell-surface expression on monocytes, 37 but it induced HLA-G expression and shedding in myeloid DCs. 38 IDO is known to be involved in the generation of tolerogenic microenvironments by tryptophan depletion and in the generation of Tregs.…”
Section: Myeloid Apcs That Express Hla-gmentioning
confidence: 99%